From the April revolution to times of austerity in Portugal: a portrait of poverty, social exclusion and inequalities - Pinto, Hugo (2017)
In the last forty years Portugal was confronted with a series of transformations. The revolutionary process of April 1974 and the European integration drove the country towards the economic policy convergence of the most developed member-states of European Union. This approach was slowing since the beginning of the Millennium, reversed with the advent of the economic and financial crisis in 2007. The crisis generated a response on austerity policies, with deep impacts on public policy with consequences in different dimensions. Poverty, a persistent phenomenon in Portugal, affecting hundreds of thousands of families in the last decades, increased with the crisis. This article discusses ideas about poverty, social exclusion and inequality, to analyze in synthetic form the recent evolution of the Portuguese case in the context of austerity.